Uji Efektivitas Kombinasi Ekstrak Daun Kemangi (Ocimum x africanum Lour.) dan Daun Pandan Wangi (Pandanus amaryllifolius Roxb.) Terhadap Larva Aedes aegypti - Wati, Ria Widya; Nofita, Nofita; Marcellia, Selvi (Faculty of Medicine and Health Science, Universitas Islam Negeri Maulana Malik Ibrahim, 2024)
Basil leaves and fragrant pandanus leaves have secondary metabolite compounds namely alkaloids, flavonoids, saponins, tannins, and terpenoids that can be natural larvicides. The purpose of this study was to determine the activity, effectiveness and LC50 value of the combination of basil leaf extract (Ocimum x africanum Lour.) and fragrant pandanus leaf (Pandanus amaryllifolius Roxb.) as larvicide of Aedes aegypti mosquitoes. Extraction using maceration method with 96% ethanol solvent. This study used 5 treatments, namely negative control (distilled water), positive control (abate 1%), FI ( Basil leaf extract 1% concentration + fragrant pandan leaves 2% concentration), FII (Basil leaf extract 1,5% concentration + fragrant pandan leaves 1,5% concentration), and FIII (Basil leaf extract 2% concentration + fragrant pandan leaves 1% concentration) each treatment containing 25 Aedes aegypti instar III larvae with 5 repetitions. Data obtained will be analyzed by one way ANOVA test, Post Hoc Test LSD (Least Significance Different) test, and Probit test. The results of the effectiveness test on FIII with a mortality value of 100%, said to be effective in killing Aedes aegypti larvae. The results of the one way ANOVA test showed significant differences in average concentrations, then the results of the LSD Post Hoc Test showed that the FIII concentration had larvicidal effectiveness that was not significantly different from the positive control, this can be seen from the significant value of 1.000 (p>0.05) against the positive control. The probit test results showed an LC50 value of 1.715% which means that the combination of basil leaf extract (Ocimum x africanum Lour.) and fragrant pandanus leaf (Pandanus amaryllifolius Roxb.) has toxic properties as a natural larvicide Keyword : Basil Leaf, Fragrant Pandanus Leaf, Larvicide, Aedes aegypti